2015
DOI: 10.18632/oncotarget.4204
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibitsin vitroandin vivochronic myelogenous leukemia cells growth: a possible role for exosomal disposal of miR-21

Abstract: Exosomes are nanosize vesicles released from cancer cells containing microRNAs that can influence gene expression in target cells. Curcumin has been shown to exhibit antitumor activities in a wide spectrum of human cancer. The addition of Curcumin, to Chronic Myelogenous Leukemia (CML) cells, caused a dose-dependent increase of PTEN, target of miR-21. Curcumin treatment also decreased AKT phosphorylation and VEGF expression and release. Colony formation assays indicated that Curcumin affects the survival of CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 42 publications
5
83
0
Order By: Relevance
“…Finally, it maybe resulted from the selective package and secretion process of circulating miRNA. Previous reports showed that the expression pattern of some miRNAs in intracellular was contrary to that in extracellular owing to the selective disposal363738.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, it maybe resulted from the selective package and secretion process of circulating miRNA. Previous reports showed that the expression pattern of some miRNAs in intracellular was contrary to that in extracellular owing to the selective disposal363738.…”
Section: Discussionmentioning
confidence: 93%
“…Patients with a low plasma miR-215 expression had a significantly higher total imatinib intake compared to patients with increased miR-215 expression [13]. miR-21 was enriched in exosomes released by K562 and LAMA84 cells after treatment with curcumin, suggesting that selective packaging of miR-21 in the exosomes may contribute to the antileukemic effect of curcumin in CML [14].…”
Section: Research Papermentioning
confidence: 97%
“…Curcumin also induced the up-regulation of miR-196b and a decrease of BCR-ABL at mRNA and protein level. For these reasons, curcumin can be considered a promising compound that in association with conventional tyrosine kinase inhibitor, may improve the therapeutic approach for CML patients resistant to Imatinib [21]. Moreover, exosomes containing miR-21 and released by CML cells treated with curcumin were able to modulate the endothelial barrier organization and attenuated the angiogenic phenotype.…”
Section: Curcuminoidsmentioning
confidence: 99%